PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP DAYA INGAT DAN HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM KELAS XI IPA SMA KEMALA BHAYANGKARI 1 SUNGAI RAYA - Sahara Sahara; Dedeh Kurniasih; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACT The process of learning chemistry which only focused on teacher as informant caused the students’ memory lower. This could make the students’ learning outcomes lower, thus, it was needed STAD type of Cooperative Learning Method which had the process of interaction between student and teacher, and could help the students comprehend the material. Therefore, it was necessary to make a research which had the purpose to know the difference between students’ learning outcomes and memory which used STAD type ofCooperative Learning Method and lectures teaching method as well as how large the effect of STAD type of Cooperative Learning Method on salt hydrolysis material was. This research was Quasi Experimental Nonequivalent Control Group Design. The sample of the research was choosen by using saturated sampling which XI IPA 1 as experimental class and XI IPA 2 as control class. The techniques of data collection used measurement technique, observation, and interview while the tools of data collection used tests such as essayquestion, observation sheet, and interview guide. The statistical analysis of posttest result using U-man whitney test obtained significant value 0.000. This value was smaller than α (0.005) which meant that there was difference in learning outcome between experimental and control class. The statistical analysis result of U-man whitney delayed test obtained significant value 0.006, this value was smaller than α (0.005) which meant that there was difference between students’ memory in experimental and control class. The calculation of effect size showed value 1.64 with high criteria which gave high effect on students’ learning outcomes which was 44.95%, while the calculation of students’ memory effect size showed value 0.69 with moderate criteria which gave effect on students’ memory which was 26,42%. Keywords : Memory, Learning Outcomes, Salt Hydrolysis, STAD type of Cooperative Learning Method